Penerapan Desain Interior dan Arsitektur ke dalam Konsep Bisnis Dekorasi Acara - Andre Soenarto; Tri Noviyanto Utomo; Maria Yohana Susan (Universitas Ciputra Surabaya, 2015)
Along with the development era, Indonesia is experiencing growth in the field of economy and culture. One of the culture break from the Indonesian population lifestyle happens in holding an event. Business in the daily work does not allow them to plan their own events thus require assistance from other party organizer. This opportunity is one of the main reasons of Event Planner and Event Decoration thrive in big cities, and including in Semarang. As the capital and largest city in Central Java, Economy of Semarang city has attracted many investors to come and do some business. By relying on the captive market as well as the partner that has been built over the years Serotonin Event Planning And Decoration trying to participate in this entertainment world through decoration event as the main product. By targeting the high-end community in Semarang, Serotonin will focus on the highest segment in the economy class in Semarang. One of the regular events of this Event Decoration is the weddings and birthdays, therefore, this final project is designing three thematic concept which are chinese and traditional concept for wedding event and steampunk for birthday party. This even itself will be attended by a lot of people as guests so it takes marvelous decoration besides the event itself should not be boring as well. Serotonin will improving the requirement of design complexity for the events that are not faced by other Decoration Event that usually limited to the decoration itself, therefore this will be the main difference between Serotonin with other similar companies. Interior Architecture background also will affecting in design process from the design stage up to final design presentation that will be our distinctive characteristic.